2022
DOI: 10.1002/ca.23941
|View full text |Cite
|
Sign up to set email alerts
|

Positional deformation of the parotid gland: Application to minimally invasive procedures

Abstract: Anatomical studies of the parotid gland are important for mid-and lower face filler, botulinum toxin, and thread lifting procedures. The purpose of this study was to observe the topographic anatomy of the parotid gland using cadaveric dissections.The superficial lobe of the parotid gland was studied in 30 hemisected heads. Reference lines were made on the lateral aspect of the face. A reference line (the line connecting the mandibular angle to the upper margin of the zygomatic arch, along the posterior border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The parotid gland is an inverted-pyramidal-shaped organ that lies on the posterior border of the mandible angle [ 56 , 74 ]. Due to congenital, iatrogenic, or acquired conditions, BoNT in the glands plays a role in the esthetically slimming volume of the hypertrophic glands.…”
Section: Resultsmentioning
confidence: 99%
“…The parotid gland is an inverted-pyramidal-shaped organ that lies on the posterior border of the mandible angle [ 56 , 74 ]. Due to congenital, iatrogenic, or acquired conditions, BoNT in the glands plays a role in the esthetically slimming volume of the hypertrophic glands.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies on the parotid gland's anatomical location 6,11 . A recent study showed that the border of the parotid gland varies from the inferior margin of the zygomatic arch to the anterior part of the sternocleidomastoid muscle 12 . Clinical ultrasound findings show that the parotid gland is often distributed widely.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 11 A recent study showed that the border of the parotid gland varies from the inferior margin of the zygomatic arch to the anterior part of the sternocleidomastoid muscle. 12 Clinical ultrasound findings show that the parotid gland is often distributed widely. In addition, an accessory lobe of the parotid gland is seen in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…The study of fresh cadaveric movements of facial skin and tissues concerning postural changes reveals that transitioning from a seated to a supine position not only alters the positioning of the cadaver's head but also induces overall tension in the facial skin and soft tissues 9 . The skin and connective tissues around the head and ears are drawn, causing a visible change in the shape and angle of the periorbital area and nasal tip.…”
Section: Smas Repositioning Techniquementioning
confidence: 99%
“…The study of fresh cadaveric movements of facial skin and tissues concerning postural changes reveals that transitioning from a seated to a supine position not only alters the positioning of the cadaver's head but also induces overall tension in the facial skin and soft tissues. 9 The skin and connective tissues around the head and ears are drawn, causing a visible change in the shape and angle of the periorbital area and nasal tip. Notably, the transformation of the lower face tissues is intriguing as it demonstrates that, with postural changes, the lax skin and tissues, including those around the submental area, do not solely migrate toward the head and ears but also remain along the firm structures encompassing the chin, anterior jawline, and the angle of the mandible.…”
Section: Smas Repositioning Techniquementioning
confidence: 99%